The roles of surface soil carbon and nitrogen in regulating the surface soil pH and redox potential of sulfidic soil materials of acid sulfate soils - Michael, P. S. (2020)
Acid sulfate soils (ASS) have been described as the “nastiest” soils on earth because of their harmful impacts on various soil and environmental systems. ASS pose no problems unless the sulfidic soil materials are disturbed or exposed and the sulfides are oxidized, leading to production of sulfuric soil materials and generation of sulfuric acidity. In sulfidic soil, unless there is disturbance or exposure in the deep soil, only the surface soil seems to be frequently exposed and disturbed, leading to oxidation as a result of oxygen penetration. We have reported recently the importance of soil carbon and nitrogen in amelioration of ASS but the roles on the surface soil was not clearly established. In this study, the roles of surface soil carbon and nitrogen in regulating the surface soil redox potential (Eh) and pH of sulfidic soil material of ASS was investigated following the addition of different sources of soil carbon and nitrogen. The results showed the mechanisms involved in curtailing of sulfidic soil material oxidation and acidification were dependent on the type of metabolic substrates and the microbial ecology the resources were capable of establishing. Addition of a single nutrient source, e.g. glucose, capable of engaging a few soil microbes, was ineffective in preventing sulfidic soil oxidation, whereas addition of complex metabolic substrates, e.g. organic matter, as a source of multiple resources for microbial metabolism effectively reduced the Eh and highly increased the pH, even under aerobic soil conditions.